Gingival crevicular fluid lipocalin‐2 and semaphorin3A in stage III periodontitis: Non‐surgical periodontal treatment effects. (25th April 2022) - Ceylan, Merve; Erbak Yilmaz, Huriye; Narin, Figen; Tatakis, Dimitris N.; Saglam, Mehmet
Abstract: Background and Objective: Identification of biomarkers to assess individual risk and monitor periodontal health status is important. Research on lipocalin‐2 (LCN2) and semaphorin3A (Sema3A) is lacking. This study aimed to evaluate gingival crevicular fluid (GCF) LCN2, Sema3A, and tumor necrosis factor‐α (TNF‐α) levels in periodontally healthy (H), gingivitis (G), and periodontitis (P) patients, and their changes following non‐surgical periodontal therapy. Methods: Sixty systemically healthy and non‐smoker participants, diagnosed as periodontally healthy, gingivitis, and stage III grade C periodontitis, were recruited ( n = 20/group). Clinical periodontal parameters were recorded and GCF samples were obtained at baseline from all groups; for group P, these were repeated one and three months following non‐surgical periodontal treatment. GCF LCN2, Sema3A, and TNF‐α levels were evaluated with enzyme‐linked immunosorbent assay. Results: GCF LCN2, Sema3A, and TNF‐α total amounts were significantly higher in disease groups than group H ( p < .001). Between P and G groups, only TNF‐α levels were significantly different ( p < .001). Non‐surgical periodontal therapy resulted in significant improvement of all clinical parameters and significant decreases of GCF LCN2 and TNF‐α levels, at both time points, compared with baseline ( p < .001). Sema3A levels remained unchanged following treatment ( p > .05). LCN2 and TNF‐α levels were significantly positively correlated with clinical parameters. LCN2 (AUC [area under the curve] = 0.94) and TNF‐α (AUC = 0.98) levels were similarly accurate in differentiating between periodontal disease (whether G or P) and healthy controls. Conclusions: LCN2 and TNF‐α levels in GCF are correlated with clinical parameters and could prove useful as non‐invasive screening tools for periodontitis.